Naevus Lipomatosus Cutaneous Superficialis - Ramanan C; Ghorpade A; Das M N; Mercy P; Bose U (Wolters Kluwer Medknow Publications, 2001)
Naevus lipomatosus cutaneous superficialis (NLCS) in an eighteen year old female is reported. She had asymptomatic nodules and plaques on her lower back since birth. The diagnosis was confirmed by histopathology